Getting lost to be found: the insider–outsider paradoxes in relational ethnography. Issue 4 (23rd July 2018) - Yeo, Roland; Dopson, Sue
Abstract : Purpose: The purpose of this paper is to draw on the direct experience of a practitioner undertaking real-time research in his organization to offer insights into the dual role of practical insider and theoretical outsider. The duality helps the researcher to live "in" and think "out" of the research context to develop a theory for practice and then transpose it to a practice for theory through the collaboration of an external theoretical insider. Design/methodology/approach: This is a theoretical account of the reflexive experience of the practitioner reintroducing relational ethnography, where the researcher regards processes and spaces as the objects of analysis rather than bounded groups and places. It emphasizes the relational significance of the researcher, researched, and theoretical insider in exploring the structures of relations and meanings in the field of professional practice. Findings: The paper argues that understanding the complementariness and paradoxes of the dual role helps the researcher to identify knowledge gaps and contest commonsense knowledge in search of critical knowledge and theoretical insights. The transition between the bounded (restrained) and unbounded (unrestrained) selves occurs in the holding space of research, influencing the position from which the researcher views himself, his subjects, and his social world. Originality/value: The paper extends the dimension of ethnographic research, which de-centers the authority and control of the researcher to that of the relationship between the researcher and informants, by focusing on the relational significance between the researcher, researched, and theoretical insider. This perspective gives rise to a deeper understanding of relational ethnography, seen largely in sociological research, as relevant to organizational research, where structures of relations and actions explored in real time could account for the configuration, conflict, and coordination of work practices.